Shopping Destination Image and Loyalty: Do Tourist and Resident Perceive Differently? - Erik Hendriks; Zurinawati Mohi; Lusianus Kusdibyo (Politeknik Negeri Bandung, 2021)
Research shows that shopping is a must activity of tourist and resident, and there is intense competition between shopping destinations. However, literature often gives a little attention to how a shopping destination's image impacts customer loyalty. Thus, the current study examines the shopping destination image model that incorporates the affective, cognitive, and overall images in predicting shopping loyalty of both tourist and resident. The results from 408 survey data verify the shopping destination image model's relevance in predicting both tourist and resident loyalty towards shopping destinations. The affective and cognitive image elements are the key drivers of overall image and loyalty towards tourist and resident shopping destinations. Further, this study shows a significant variation between how tourists and residents regard the effect of cognitive image on their loyalty towards a shopping destination.